Fluoroquinolone resistance in extended‐spectrum β‐lactamase‐producingKlebsiella pneumoniaein a Japanese tertiary hospital: silent shifting to CTX‐M‐15‐producingK. pneumoniae. Issue 10 (October 2017) - Higashino, Masashi; Murata, Mika; Morinaga, Yoshitomo; Akamatsu, Norihiko; Matsuda, Junichi; Takeda, Kazuaki; Kaku, Norihito; Kosai, Kosuke; Uno, Naoki; Hasegawa, Hiroo; Yanagihara, Katsunori
Abstract : Purpose. : Fluoroquinolone resistance (FQ‐r) in extended‐spectrum β‐lactamase (ESBL) producers is an urgent health concern in countries where ESBL‐producing K. pneumoniae (ESBL‐Kpn) is prevalent. We investigated FQ‐r in Japan where ESBL‐Kpn is less prevalent. Methodology. : Clinical ESBL‐Kpn isolates from 2011 to 2013 were collected in Nagasaki University Hospital. The ESBL genotypes included CTX‐M‐15, and the mechanisms of FQ‐r through plasmid‐mediated quinolone resistance (PMQR) and mutations in quinolone resistance‐determining regions (QRDRs) were examined. Clonality was analysed by enterobacterial repetitive intergenic consensus (ERIC)‐PCR and multi‐locus sequence typing was performed on selected isolates. Results/Key findings. : Thirty ESBL‐Kpn isolates, including seven levofloxacin‐resistant isolates, were obtained from different patients. An increase in CTX‐M‐15‐producing strains was observed during the study period (0/11 in 2011, 3/8 in 2012, and 5/11 in 2013). PMQR was detected in 53.3% of the isolates and aac‐(6′)‐Ib‐cr was the most common (36.7 %). ST15 was observed in 60.0% of the isolates, and for the most predominant ERIC‐PCR profiles, 62.5% of the isolates possessed the CTX‐M‐15 genotype and 71.4% were levofloxacin‐resistant. Levofloxacin‐resistance was significantly more common in CTX‐M‐15 isolates (62.5 %) compared to non‐CTX‐M‐15 isolates (9.1 %). Three QRDR mutations and aac(6′)‐Ib‐cr, but not qnrB and qnrS, were significantly enriched in the CTX‐M‐15 isolates (100.0 %) compared to the non‐CTX‐M‐15 isolates (13.6 %). Conclusion. : Cumulatively, these results indicate that the epidemic strain, the CTX‐M‐15‐producing K. pneumoniae ST15, is covertly spreading even when ESBL producers are not prevalent. Monitoring these epidemic strains and ESBLs in general is important for quickly identifying health crises and minimizing future risks from FQ‐r ESBL‐Kpn.